Customer satisfaction strategy in automotive industry - example of Škoda Auto - Jůzl, František; Machková, Hana; Malý, Josef, 1958-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The first objective of this thesis is to define the most significant benefits of a customer satisfaction strategy for a company. Especially, the effects on customer base, retention, loyalty, and last but not least on financials are discussed. Furthermore, three techniques of customer satisfaction measurement are critically assessed. Those are complaint management, customer satisfaction surveys, and mystery shopping. Secondly, a comprehensive customer satisfaction strategy for ŠKODA AUTO is defined based on theoretical knowledge regarding customer satisfaction and the specifics of automotive industry. The strategy comprises of four particular parts: generic approach, sales, after sales, and product.
Vedoucí práce: Hana Machková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses